2017
DOI: 10.1177/1352458517699875
|View full text |Cite
|
Sign up to set email alerts
|

Functional network connectivity abnormalities in multiple sclerosis: Correlations with disability and cognitive impairment

Abstract: Increased and decreased RS FC occurs in MS and contributes to a wide spectrum of clinical manifestations. RS FC reduction is related to T2 lesions. Such a paradigm is inverted for the thalamic network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
122
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 32 publications
15
122
4
1
Order By: Relevance
“…In diseased patients, the insular cortex has been implicated in motor improvement after a motor stroke (Weiller et al, ) and MS relapse (Pantano et al, ). The reduction of RS FC between the thalami and caudate nuclei, cingulate cortex and cerebellum seems to have an important role in determining motor impairment in MS, in line with the results of a recent study (Rocca et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In diseased patients, the insular cortex has been implicated in motor improvement after a motor stroke (Weiller et al, ) and MS relapse (Pantano et al, ). The reduction of RS FC between the thalami and caudate nuclei, cingulate cortex and cerebellum seems to have an important role in determining motor impairment in MS, in line with the results of a recent study (Rocca et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…After exclusion of 8 MS and one HC due to poor image quality and/or postprocessing failure, the final cohort included 187 MS patients (136 with relapsing-remitting MS, 42 with secondary progressive MS and 9 with primary progressive MS) and 94 age-and sexmatched HC. A portion of these patients was also part of two previous investigations (Rocca et al, 2016(Rocca et al, , 2017. right and left hand).…”
Section: Subjectsmentioning
confidence: 99%
“…Reduced connectivity of resting-state networks involving cortical regions was also observed in RRMS relative to HC,28 but was especially severe in SPMS 9. Recently, another study reported similar widespread increased and decreased functional connectivity changes in another cohort of patients with MS, whereby the level of functional connectivity, of especially cortical regions, decreased along the disease course, while DGM regions showed increased connectivity 18. This study showed earlier changes in decreased cortical connectivity than ours, which may be due to differences in the methodological approaches.…”
Section: Discussionmentioning
confidence: 76%
“…Resting-state functional magnetic resonance imaging (fMRI) is able to explore connectivity in predefined networks as for example the default mode network, the visual network, and the motor network. In MS, patients could experience either a decrease or an increase in functional connectivity [12][13][14][15][16]. In addition, resting-state fMRI might also depict network topography changes, through graph theoretical analyses.…”
Section: Introductionmentioning
confidence: 99%